Christian Moral Identity And Systemic Corruption In Ghana - Atsu (University of Ghana, 2020)
Structural corruption is one of the most challenging issues confronting the Ghanaian society today and it is usually identified as a reason the country is unable to achieve its developmental goals. Unfortunately, this phenomenon has posed a challenge to the Christian moral identity as a result of the increasing number (71.2%) of the Ghanaian population asserting themselves as Christians. This study was conducted to examine the problems of corruption, investigate the ethical challenges it poses to the church and discuss some responses of the church in the fight against structural corruption. A qualitative method was employed to explore the phenomenon of structural corruption. The phenomenological approach was used because it is the most appropriate research design that seeks to understand the phenomenon of corruption which is conceptualized in the thoughts of people. The Adonai Chapel-Madina, Trinity Chapel-Kotobabi and Shalom Chapel-Akatsi, of the Global Evangelical Church, were used as settings to gather data from pastors and church members comprising church workers, workers in the public sphere and synod committee members. The interview guide aided the data collection process. Findings from the study revealed that structural corruption has led to a lack of growth and development in Ghana and bribery is a major form of corruption perpetuated in the country. Findings from the study also indicated ignorance, compromise and disregard for Christian doctrines on the part of Christians as the main reasons Christians engage in corruption. Although the rate of corrupt practises in the country undermines the integrity of the church, the study further revealed that consistent use of platforms such as social media, communiques and academic publications on corruption by the church, are essential to the fight against corruption. It is recommended that the silence of the church in the face of a detrimental and deadly predicate such as corruption could infer tacit approval.
MPhil. Study Of Religion
Keywords: Ghana; Christian; Moral; Church; Social Media